From Satisfaction to Loyalty: Examining Customer Loyalty in Islamic Education - Zainal Berlian; Ade Sentia Arsy Sabila; Ikas Kasenda (Penerbit Presisi Pustaka, 2025)
Islamic educational institutions face increasingly fierce competition, making customer satisfaction and loyalty (students and parents) key to maintaining their sustainability. This article discusses the concepts of customer satisfaction and loyalty in the context of Islamic educational services, including definitions, key dimensions, and measurement methods. The research approach utilizes a literature review from various service marketing sources and a case study of an Islamic school. The study results indicate that high service quality (including the five dimensions of SERVQUAL) plays a crucial role in increasing customer satisfaction, which in turn can build long-term loyalty. However, high satisfaction does not automatically guarantee loyalty without ongoing efforts, particularly in consistently meeting customer expectations. Customer loyalty in Islamic education is reflected not only in repeat purchasing behavior but also in positive attitudes and alignment with Islamic values ​​such as monotheism and moral responsibility. By improving service quality and implementing regular satisfaction measurement and customer relationship management (CRM) strategies, Islamic educational institutions can strengthen customer loyalty and their competitiveness.